A randomized control study of titrated and oral misoprostol solution for induction of labor at term - Sharma, Barbie; Dhar, Tapasya; Goyal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Quest for an induction method with safety, efficacy, feasibility, low cost, and patient preference is a constant pursuit for all obstetricians. Oral misoprostol is one such method which has been shown to be effective in achieving vaginal birth and has been recommended by WHO (2011) and FIGO (2012) for induction of labor. This study aimed to evaluate effectiveness and safety of hourly titrated oral misoprostol solution in comparison with two hourly static-dose oral misoprostol solution for induction of labor at term. Methods: Single centre interventional single-blinded randomized controlled trial conducted in a tertiary care centre in Ludhiana. 264 term pregnant women were randomly given titrated (group A) or static oral misoprostol solution (group B) till the onset of active labor. Induction to delivery time was the primary outcome measure while the secondary outcome measures pertained to efficacy and safety of the regimens. Results: 268 women were randomized, 4 patients were excluded from analysis because of drop out, leaving 264 women for intention to treat analysis. The mean interval between induction and delivery was 16.19±10.48 hours in group A and 15.28±8.34 hours in group B (p>0.10, NS). 71 women (53.8%) in group A and 72 women (54.5%) in group B had vaginal delivery within 24 hours (p>0.10, NS). 40.9% women in group B required more than 8 hours to receive the required number of doses as compared with 8.3% women in dose group A (p<0.01, SS). Oxytocin requirement was significantly higher in group A (76.5%) as compared to group B (59.8%) (p<0.05, SS). Incidence of fetal and maternal complications, rate of cesarean section and instrumental delivery was comparable between the two groups (p>0.10, NS). Conclusions: Titrated oral misoprostol, considering its efficacy, safety and time saving is comparable to WHO recommended static oral misoprostol.